Association between Visceral Fat and Body Mass Index in Patients with Cirrhosis - Kenichiro Yasutake,; Motoyuki Kohjima,; Yusuke Murata,; Manabu Nakashima,; Makoto Nakamuta ,; Munechika Enjoji, (Journal of Pharmacy and Nutrition Sciences, 2014)
Obesity has recently become a critical problem in patients with cirrhosis in Japan; however, its true prevalence and prognosis remain poorly understood. In this study, we investigated abdominal fat areas, including subcutaneous and visceral fat areas (VFA), in 49 cirrhotic patients and analyzed the association between VFA and body mass index (BMI). Fat areas were examined by computed tomography. Patients were classified as somatometric obesity and visceral obesity based on their BMI (cut-off value: 25 kg/m2) and VFA (cut-off value: 100 cm2), respectively. The mean BMI was 23.5±3.3 kg/m2 (<25 kg/m2, 35 cases; 25 kg/m2, 14 cases) and mean VFA was 108.5±118.8 cm2 (<100 cm2, 25 cases; 100 cm2, 24 cases). Thirteen out of 14 patients with BMI 25 kg/m2 had a VFA 100 cm2, and 11 of 35 patients with BMI <25 kg/m2 had a VFA 100 cm2. Thus, almost half of the cirrhotic patients in this study had visceral obesity, including a high proportion of patients with BMI <25 kg/m2. These results suggest that visceral obesity, as well as BMI, should be considered in patients with cirrhosis, and individual nutritive management regimes should be designed according to the results.